PROCESSES OF LIQUID-PHASE RECOVERY OF SCALE IN ROTATIONAL FURNACE - S. L. Rovin; L. E. Rovin (Литьë и металлургия)
The data, enabling to establish peculiarities and distinction of liquid-phase reduction of oxides in rotation furnaces, are received as a result of laboratory and field observations.